The relationship between FMS and functional single-leg hop stabilization test in team sport and martial arts young male athletes - Pedak, K.; Bazanov, B.; Rannama, I. (World Congress of Performance Analysis of Sport XII, 2018)
Introduction: The aim of this study was to investigate the correlations between two different functional tests: Functional Movement Screen (FSM) and dynamic postural stability test results of athletes from team sport (basketball, handball, volleyball) and martial arts (judo, taekwondo, karate). Methods: 45 team sport (age =16.27 ± 1.7 years: height=183,2± 6.6 cm and BMI=23.5 ± 3.8) and 19 martial arts athletes (17,6±2,2a years: height=177,6±6,7cm and BMI=24.4±3.7). Participants were screened using the 100-point scale FMS™ protocol (Butler.R.J et al.,2010). The Dynamic Postural Stability Index (DPSI) and the directional components (medial-lateral, anterior-posterior, and vertical) after a jump landing was measured by Kistler force plates (Wikstrom, E. A et al.,2005).AII statistical analysis was computed using the IBM SPSS Statistics (version 23.0). Results: The mean composite FMS 100-point scale of martial arts athletes was 55.1±9.3 and team sports athletes 45,0±6.4. Martial arts athletes shows statistically significantly higher score in active straight-leg raise 4.4±3.1 vs 7.9±3.9 (p<0.05) and trunk stability push-up test 4.4±3.5 vs 7.1 ±4.5 (p<0,001). There was not statistically significant difference between other five tests. There was not significant differences between athletes groups stability test results. The team sport athletes shows slightly better medial- lateral stabilisations that martial arts athletes (4.4±0.53 vs 4.6±0,03) in 1 second trial duration and martila arts athletes anterior-posterior stabilisations (20.97±0.68 vs 22.2±0.15). There was moderate correlation between seven different FMS exercises scores and DPSI values of martial arts atheletes (r= 0.51) and team sports athletes (r=0,47). Conclusion: The results of the study indicate low score both tests in groups. The team sport athletes have more problems with muscles of the hamstring and trunk muscles stabilizing than martial artists. Sport specifically shows team sport athletes better medial-lateral direction posture stabilisation and martial arts anterior-posterior posture stabilsation. The relationship between functional performance ability and sport injury risk has been established in many cases, but relationship between functional performance ability and sport- specific athletic performance needs more reseach.